Mining Projects in South Africa: Aspiration Levels Versus Fairness when Negotiating Time Extension - Deysel, Roelof Jacobus (My University, 2013)
The relationship between mining companies and mining contractors is presently viewed as an adversarial relationship. During mining construction projects there are often underlying reasons for break-downs in client-contractor relationship as, for example, in the event of the client not awarding an extension of time. At this stage, the counter parties engage in re-negotiation of the completion date. The perceived wisdom is that the contractor has little bargaining power against the mining house. The purpose of this research is to establish the main reasons for the breakdown of the contractor, client relationship and to determine the positioning of the two counter parties on the Pareto curve. Using a small data sample of experts and also making use of qualitative research, semi-structured interviews were used to test the perceptions and opinions of these experts in order to assess and to understand the bargaining power position of the counter parties at the end of the project. The key findings were, that contractors profit from both constructive acceleration and extension of time. The general perception of the contractor’s poor bargaining position is often incorrect. It is also evident that close control on the project contract is extremely important and that the success of the project is ultimately closely related to the maturity of the contractor-client relationship, also, that quick action and reaction on scope variances are extremely important.
MBA thesis
Keywords: Mines and mining; Mining projects; Project time extension